1997
DOI: 10.1002/(sici)1096-8652(199704)54:4<288::aid-ajh5>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Differences between platelet phosphoinositide metabolism stimulated by thrombin or SFLLRN are not accounted for by interaction of thrombin with glycoprotein Ib

Abstract: The formation of inositol phosphates was compared in aspirin-treated, washed human platelets suspended in Tyrode's-albumin solution containing 2 mM calcium and stimulated with SFLLRN (thrombin receptor-activating peptide) or thrombin. SFLLRN (20 µM) and thrombin (1 U/ml) resulted in maximal irreversible aggregation and 80-90% secretion of dense granule contents. SFLLRN (50-100 µM) caused larger increases at 10 sec than 20 µM SFLLRN in the formation of inositol trisphosphate (IP 3 , measured as [ 3 H]inositol l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For example, primary ADP-induced aggregation, which is not influenced by r-apo(a), does not involve the activation of intracellular phospholipase C, 46 whereas SFLLRN-induced responses, which are enhanced by both r-apo(a) and Lp(a), involve activation of phospholipase C, leading to hydrolysis of phosphatidylinositol 4,5-bisphosphate. 47,48 Stimulation of platelets with thrombin also activates phospholipase C, and Gries et al 16 reported that maximal platelet aggregation stimulated by 0.1 U/mL thrombin was not affected by Lp(a). However, it is not possible to observe an enhancement of a response that is already maximal.…”
Section: Discussionmentioning
confidence: 99%
“…For example, primary ADP-induced aggregation, which is not influenced by r-apo(a), does not involve the activation of intracellular phospholipase C, 46 whereas SFLLRN-induced responses, which are enhanced by both r-apo(a) and Lp(a), involve activation of phospholipase C, leading to hydrolysis of phosphatidylinositol 4,5-bisphosphate. 47,48 Stimulation of platelets with thrombin also activates phospholipase C, and Gries et al 16 reported that maximal platelet aggregation stimulated by 0.1 U/mL thrombin was not affected by Lp(a). However, it is not possible to observe an enhancement of a response that is already maximal.…”
Section: Discussionmentioning
confidence: 99%
“…Several discrepancies in platelet responses have been noted when platelets are stimulated by thrombin versus SFLLRN in vitro (8)(9)(10)(11)(12). These differences may be due in part to the presence of both PAR1 and PAR4 on human platelets (5,6).…”
mentioning
confidence: 99%